O humor na obra infantil de André Ricardo Aguiar - Farias, Angelina Silva de (2022)
This dissertation aims to analyze the humor element present in André Ricardo Aguiar's children's work. In a more specific way, to present the books: O rato que roeu o rei (2007), Pequenas reinações (2012) and Chá de sumiço e Outros poemas assombrados (2013), as being these productions for the children's public in the bias of contemporaneity, comprehending the process of dialogue between the books and the scenario of the century's mutations for the realization of humor. In this sense, it is justified both by the literary quality of the writings of the aforementioned writer from Paraíba and by the lack of critical works about his work and the proposed subject, which made us believe that the research is significant in contributing to the establishment of the critical fortune. The corpus of this research is the before mentioned books, and it is through them that we seek to confirm the hypothesis raised: that of a process of meaning that took place through laughter, using elements such as jokes, word games, puns, reaching to a poetic construction in children's literature averse to utilitarian and pedagogic, works that establish themselves as children's production concerned with aesthetics. To support the analysis, texts by Bergson (2018), Freud (1905), Todorov (1980), Candido (1996), Hunt (2010), Bosi (1996), Ribeiro Neto (2015), Candido (1983), Barbosa Filho (2001), among others, were used. As a result, we observe a process of (re)signification that is not restricted to the exchange of place of the characters based on their characteristics, but that happens through elaborate work with the word, achieving a refined humor.